Hydrogen Sulfide Protects against Chronic Unpredictable Mild Stress-Induced Oxidative Stress in Hippocampus by Upregulation of BDNF-TrkB Pathway - Hu, Min (Oxid Med Cell Longev, 2016)
Chronic unpredictable mild stress (CUMS) induces hippocampal oxidative stress. H(2)S functions as a neuroprotectant against oxidative stress in brain. We have previously shown the upregulatory effect of H(2)S on BDNF protein expression in the hippocampus of rats. Therefore, we hypothesized that H(2)S prevents CUMS-generated oxidative stress by upregulation of BDNF-TrkB pathway. We showed that NaHS (0.03 or 0.1 mmol/kg/day) ameliorates the level of hippocampal oxidative stress, including reduced levels of malondialdehyde (MDA) and 4-hydroxy-2-trans-nonenal (4-HNE), as well as increased level of glutathione (GSH) and activity of superoxide dismutase (SOD) in the hippocampus of CUMS-treated rats. We also found that H(2)S upregulated the level of BDNF and p-TrkB protein in the hippocampus of CUMS rats. Furthermore, inhibition of BDNF signaling by K252a, an inhibitor of the BDNF receptor TrkB, blocked the antioxidant effects of H(2)S on CUMS-induced hippocampal oxidative stress. These results reveal the inhibitory role of H(2)S in CUMS-induced hippocampal oxidative stress, which is through upregulation of BDNF/TrkB pathway.